AN INVESTIGATION INTO THE OCCURRENCE OF SPEAKING ERRORS IN THE UTILIZATION OF THE SIMPLE PRESENT TENSE AMONG JUNIOR HIGH SCHOOL STUDENTS - Himni, M Saleh Yahya; Sulhairi, Sulhairi (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2025)
The objective of this paper is to identify the type of errors that occurred in the spoken language of eighth-grade students at SMP Islam Pancor Kopong. The present study employs a qualitative research design. The objective of this study was to analyze the errors made by eighth-grade students at SMP Islam Pancor Kopong when using the simple present tense. The data were collected through a spoken test. The researcher poses questions to the student regarding their daily activities. This evaluation is designed to identify errors in spoken language production. The findings of this study are as follows. The researcher identified various types of errors, including omission, addition, mis-formation, and mis-ordering. The most prevalent error type was omission, with 29 errors, accounting for 39.19% of the total. This was followed by mis-formation, with 20 errors, constituting 27.03% of the total. Additional errors included addition, with 14 errors, amounting to 18.92%, and mis-ordering, with 11 errors, making up 14.86% of the total.